Intracerebral Hemorrhage: A Brief Evidence-Based Review of Common Etiologies, Mechanisms of Secondary Injury, and Medical and Surgical Management - Sarma, Anand K.; Ghoshal, Shivani; Craven, Spencer J.; Sarwal, Aarti (Journal of Neuroanaesthesiology and Critical Care, 2019)
Intracerebral hemorrhage (ICH) accounts for only 10 to 15% of all strokes but remains a significant cause of morbidity and mortality. Despite lengthy stays in critical care units, only one-half of those experiencing an ICH survive after 30 days, and those who do are often left with considerable disability. Treatment has traditionally focused on minimizing the hemorrhage expansion and reducing clot volume through both medical and surgical means. Management of ICH is a complex and multidisciplinary process. This review will discuss a few common etiologies, explore the pathophysiology of secondary neuronal injury after ICH, review the basics of ICH imaging with computed tomography and magnetic resonance imaging, and highlight latest practices in medical and surgical management. Secondary injury mechanisms such as perihematomal edema and disordered cerebral autoregulation are discussed as potential targets for new treatment modalities. Emergent treatment in the “golden hour” after ictus provides a template of measures to adopt from initial contact with emergency medical services, to the emergency department, and thereafter, triage to the intensive care unit. Medical management including blood pressure control, hemostasis, and coagulopathy reversal are discussed and evidence from trials such as INTERACT 2, ATACH 2, and ANNEXA-4 are given a clinical context. Surgical management including intracranial pressure monitoring, surgical evacuation with open craniotomy, and minimally invasive approaches such as stereotactic-guided aspiration and thrombolysis, ultrasound-induced thrombolysis, image-guided stereotactic endoscopic aspiration, and stereotactic ICH underwater blood aspiration are enumerated. The outcomes and relevance of STICH, MISTIE, and CLEAR trials to present surgical care are elaborated. The review summarizes the current guidelines for the treatment of ICH and the latest literature in the field they are based upon. It aims to provide a concise article beneficial to the emergency physicians and neurointensivists/neuroanesthesiologists.
Keywords: coagulopathy reversal; intracerebral hemorrhage; management; minimally invasive; perihematomal edema